An ethical approach to resolving value conflicts in child protection. Issue 1 (15th June 2009) - Webb, E; Moynihan, S
Abstract : Child protection professionals working in diverse societies are regularly faced with value conflicts. Recognising these, and resolving them in the best interests of children, is a task that requires child protection specialists to make complex judgements and decisions. In this paper the philosophical concepts of absolutism and relativism to child abuse are applied, and it explores how this approach has practical relevance to solving ethical dilemmas in child protection. Children's interests are best served by erring towards an absolutist approach to the diagnosis and recognition of maltreatment and towards a relativistic approach in determining how services respond to a harmful incident or situation. Absolutism and relativism are not alternatives, but part of a continuous process of recognising and negotiating ever-changing community, national and global norms. At the service level the dichotomy transpires into the need to be culturally competent in handling the conflicting needs, rights and values of children, families, communities and professionals, whilst retaining the skill of child advocacy.